1990
DOI: 10.3928/0147-7447-19900501-18
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment of Posttraumatic Chondromalacia Patellae

Abstract: An arthroscopic procedure of excision of damaged cartilage and drilling the subchondral bone plate for treatment of chondromalacia patellae is described. Satisfactory results and absence of major complications are reported in a preliminary, short-term series of 24 cases of symptomatic posttraumatic chondromalacia patellae, with a mean follow up of 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Two studies found that most patients were satisfied with their results after surgery. 18,21 Zorman et al 17 reported relief of preoperative pain and ability to resume motor activity identical to that of the pretraumatic situation in the majority of their patients. Gobbi et al 20 found improvement in the Tegner score after microfracture in the PFJ.…”
Section: Clinical Outcomesmentioning
confidence: 95%
See 3 more Smart Citations
“…Two studies found that most patients were satisfied with their results after surgery. 18,21 Zorman et al 17 reported relief of preoperative pain and ability to resume motor activity identical to that of the pretraumatic situation in the majority of their patients. Gobbi et al 20 found improvement in the Tegner score after microfracture in the PFJ.…”
Section: Clinical Outcomesmentioning
confidence: 95%
“…Zorman et al 17 McCarroll et al 18 Steadman et al 9 Gobbi et al 20 Kreuz et al 19 found that patients aged 40 years or older had improved outcomes compared with those younger than 40 years after microfracture in the PFJ, favoring the theory that younger patients have greater regenerative capacity. They also demonstrated worse outcome scores in all patients between 18 and 36 months postoperatively that was notably less pronounced in younger patients.…”
Section: Factorsmentioning
confidence: 99%
See 2 more Smart Citations